2022
DOI: 10.1212/wnl.0000000000200518
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Headache Characteristics and a Remote History of TBI in Veterans

Abstract: Objective:To examine the association between deployment-related Traumatic Brain Injury (TBI) severity, frequency, and other injury characteristics on headache outcomes in veterans evaluated at a Veterans Administration (VA) polytrauma support clinic.Methods:We conducted a retrospective chart review of 594 comprehensive TBI evaluations between 2011-2021. Diagnostic criteria were based upon the Department of Defense/VA Consensus-Based Classification of Closed TBI. Adjusted Odds Ratios and 95% Confidence Interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…First, various criteria have been used to define the severity of TBI. These include the duration of loss of conscious [ 44 ], Glasgow Coma Scale score [ 5 , 36 , 45 ], and duration of post-traumatic amnesia (PTA). A recent study even identified more than 50 definitions for mild TBI [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, various criteria have been used to define the severity of TBI. These include the duration of loss of conscious [ 44 ], Glasgow Coma Scale score [ 5 , 36 , 45 ], and duration of post-traumatic amnesia (PTA). A recent study even identified more than 50 definitions for mild TBI [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study revealed that patients who continued to experience headaches three months after TBI were more likely to exhibit slow continued recovery, particularly after a year of persistent headaches and particularly if their TBI was moderate or severe [ 17 ]. Another study revealed that patients with a history of moderate TBI had higher odds of reporting severe headaches (adjusted odds ratio: 3.89) and migraine-like features (adjusted odds ratio: 15.34) than those with subconcussive exposure, which was limited to mild TBI [ 44 ]. Furthermore, a study revealed that moderate and severe TBI can disrupt the blood–brain barrier and thus allow the migration of neutrophils from leaky blood vessels, resulting in neuroinflammation, which plays a key role in the pathophysiology of post-traumatic headache [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate Dr. Gupta's comments on our article, 1 but respectfully disagree. Our findings indicate clinicians may achieve a more precise prognosis of traumatic brain injury (TBI)–related headaches by eliciting a detailed history of TBI frequency and severity (subconcussive, mild, or moderate), loss of consciousness duration, alterations of consciousness, and posttraumatic amnesia as semicontinuous variables rather than categorical criteria.…”
mentioning
confidence: 86%
“…Androulakis et al advance the classification of traumatic brain injury (TBI)-associated migraine-like headache in army veterans and focus on remote retrospective multidimensional and cumulative effect. 1 Paradoxically, their data suggest mild/multiple TBI, moderate TBI, and a longer duration as being statistically more contributory toward headache than other factors, besides alteration of consciousness. Conversely, alterations of consciousness and post-traumatic amnesia for longer than 30 minutes are associated with more severe headache.…”
mentioning
confidence: 97%
“…Conversely, alterations of consciousness and post-traumatic amnesia for longer than 30 minutes are associated with more severe headache. 1 None of the TBI phenotypes offer any clue to pronociceptive ophthalmic trigeminal (V1) neural activations or their link with the eye. 2 The investigators do not comment on the role of cortical spreading depression (CSD) in migraine.…”
mentioning
confidence: 99%